How does forest fertilization influence tree productivity of boreal forests? An analysis of data from commercial forestry across Sweden - Boeraeve, Margaux; Lindahl, Björn; Engelbrecht Clemmensen, Karina; Strengbom, Joachim (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2025)
Forest fertilization is a forest management practice that is often claimed to increase productivity in boreal forests. Although regarded as an efficient way to increase profitability, it is also costly, and associated with risks such as biodiversity loss and nitrogen leaching from the soil. To be both cost-efficient and sustainable, potential enhanced productivity due to fertilization should be balanced against the adverse environmental impact. One effective strategy is to limit fertilization to sites where it can most significantly increase tree productivity, while avoiding application in less suitable areas. However, the current understanding of the specific conditions under which forest fertilization optimally stimulates tree growth is limited. To clarify this, we analysed standing tree volume from 32,498 recently harvested fertilized and unfertilized stands from Sweden's largest forest owner. We applied generalized additive models to quantify the effect of fertilization on standing tree volume at harvest and how the fertilization effect depended on dominant tree species, stand characteristics (site index, stem density), climatic conditions (temperature sum), and management (thinning, stand age at harvest). We found that the effect of operational fertilization was highly context-dependent. In pine-dominated stands, fertilization failed to increase tree volumes in cold climates and low-productive stands. In spruce-dominated stands, fertilization did not result in increased tree volumes in low-productive and high-productive stands. For a more sustainable and cost-efficient application of this practice we suggest that the context dependency of the efficiency of fertilization is given more attention. Hence, we recommend to refrain from fertilizing pine-dominated stands situated on lowproductive land or in regions with cold climates, such as those found in northern Sweden.